Performance analysis of ZigBeePRO network using shortest path algorithm for Distributed Renewable Generation - Islam, Syed Zahurul; Othman, Mohammad Lutfi; Islam, Syed Zahidul (Kaunas University of Technology, 2021)
The communication requirement for integrating Distributed Renewable Generation (DRG) into Smart Grid (SG) is not strict, where the reliability and critical demand of data delivery are compromised due to the low-data rate and power of ZigBee. However, the presence of various dielectric constant materials in the DRG can cause transmission impairments of the electromagnetic wave. In this paper, we have analysed the performance of the ZigBeePRO network by applying the shortest path algorithm while delivering energy data from the solar DRG to the SG. The DRG architecture is created by considering a real test-bed of 35 kW solar DRG at Universiti Putra Malaysia (UPM). The numbers of nodes are calculated from specifications of the ZigBeePRO enabled Waspmote embedded board, inverters, and electrical parameters of a Photovoltaic (PV) module. The results of the obtained propagation path loss model indicate that the Transverse Electric (TE) and Transverse Magnetic (TM) polarizations are proportional to the loss of the propagation path at different incident angles (α); however, an exception is observed for the TM polarization at α = 55 o. Due to this polarization effect, the brick-built type cabin at the DRG site is a consequence of a higher propagation path loss than the Iron (III)-made cabin. The other performance parameters, including network throughput, data loss, and ZigBeePRO collision, are also evaluated.